A Case of Intravascular Diffuse Large B-Cell Lymphoma Initially Suspected as Interstitial Pneumonia Associated With Systemic Scleroderma. (March 2021) - Oguri, Tomoyo; Sasada, Shinji; Aramaki-Sumii, Yuki; Tsuchiya, Yumi; Ishioka, Kota; Takahashi, Saeko; Kunieda, Hisako; Kimura, Yoshifumi; Seki, Reishi; Hirose, Shigemichi; Nakamura, Morio
Intravascular large B-cell lymphoma (IVLBCL) is a rare form of diffuse LBCL. The patient was a 71-year-old female admitted to our hospital with hypoxia. On admission, chest computed tomography revealed a ground-glass opacity. Interstitial pneumonia associated with systemic scleroderma was suspected because of positive anti-centromere antibody. Thereafter, steroid pulse therapy and plasma exchange were performed. Although ground-glass opacity improved, bilateral pleural effusion appeared, so we performed a random skin biopsy because of her elevated serum lactate dehydrogenase and soluble interleukin-2 receptor levels. The patient was diagnosed with IVLBCL with symptoms improving after 6 cycles of rituximab plus chemotherapy treatment.